A Luciferase Mutant with Improved Brightness and Stability for Whole-Cell Bioluminescent Biosensors and In Vitro Biosensing - Maria Maddalena Calabretta; Denise Gregucci; Héctor Martínez-Pérez-Cejuela; Elisa Michelini (Biosensors, 2022)
The availability of new bioluminescent proteins with tuned properties, both in terms of emission wavelength, kinetics and protein stability, is highly valuable in the bioanalytical field, with the potential to improve the sensitivity and analytical performance of the currently used methods for ATP detection, whole-cell biosensors, and viability assays among others. We present a new luciferase mutant, called BgLuc, suitable for developing whole-cell biosensors and in vitro biosensors characterized by a bioluminescence maximum of 548 nm, narrow emission bandwidth, favorable kinetic properties, and excellent pH- and thermo-stabilities at 37 and 45 °C and pH from 5.0 to 8.0. We assessed the suitability of this new luciferase for whole-cell biosensing with a cell-based bioreporter assay for Nuclear Factor-kappa B (NF-kB) signal transduction pathway using 2D and 3D human embryonic kidney (HEK293T) cells, and for ATP detection with the purified enzyme. In both cases the luciferase showed suitable for sensitive detection of the target analytes, with better or similar performance than the commercial counterparts.